A lesson in propriety - Turano, Jen (Merriweather Academy for Young Ladies, 2025)
"With her father dead, her fortune stolen, and her fiancé casting her aside, Miss Drusilla Merriweather's privileged life has been upended. She is left with only one option: to provide for her family by opening a finishing school in the allegedly haunted castle she's inherited from her eccentric aunt. However, her plan is immediately threatened by unscrupulous developers keen on claiming the coveted estate for themselves by any means necessary. Mr. Rhenick Wittenbecker, a dashing architect with a tendency to charm his way out of trouble, is convinced he can protect Drusilla but is challenged by her fierce independence. Yet when strange occurrences--walking suits of armor and unexpected ghostly visitors--arise within the castle's grounds, Drusilla must decide whether to risk her family's safety and her school on the gallant architect who seems to have found his way into her heart."--